OMNIBUS LAW IN INTERNATIONAL HUMAN RIGHT LAW PERSPECTIVE (FOCUS ON LABOR RIGHT IN INDONESIA) - Nuriskandar, Lalu Hendri; Muzawir, Muzawir; Suarajana, Suarjana; Adnan, Idul (PRODI HUKUM TATANEGARA, 2023)
There is a Bill titled All Lawis one of the government's progressive steps in the legal sector. This is allegedly due to President Joko Widodo's anger at Indonesia's sluggish progress in the investment sector. Based on reports Ease Of Doing Business 2019, Indonesia is ranked 73rd out of 190 countries. Formation All Law especially in the economic sector, it is hoped that it will be able to improve the investment climate in Indonesia, Rosan Roeslani said that one of the objectives of the law to all This is to improve Indonesia's ranking in Ease od doing Business. In legal research, there are two research approaches, namely a normative approach and a sociological juridical approach. Meanwhile, what is used to examine the data are theories commonly known in doctrinal legal theory such as legal rules, legal principles, legal definitions and so on. In this case, law to all What is meant in the Indonesian legal system is a form of law that regulates various objects in one legal instrument. so that there is a spread of discourse regarding the omnibus law which is equated with the Umbrella Law, namely a law that is the parent of other laws that are still in the same sector. However, if law to all narrated as an Umbrella Law, the law to all is not regulated in Law Number 12 of 2011 concerning the Formation of Legislative Regulations, therefore law to all in the Indonesian context, it is narrated as a law. The protection of human rights (HAM) was originally known in the social contract theory put forward by Rousseau. Based on social contract theory, the rights owned by everyone are handed over to the state based on free will. The state's duty is to provide protection to every citizen if there is a violation of the rights of citizens to achieve order and justice. Keywords : Human Right, International, Labor